Performance Evaluation of Diagnostic Methods for Schistosoma mansoni Detection in Amhara Region, Northwest Ethiopia. (19th October 2020) - Fenta, Abebe; Hailu, Tadesse; Alemu, Megbaru; Amor, Arancha
Abstract : Background . Schistosoma mansoni is a parasitic worm that infects humans throughout the world. It is more prevalent in sub-Saharan Africa including Ethiopia. Proper detection of Schistosoma mansoni using sensitive diagnostic methods is crucial in the prevention and control era. Since direct wet mount microscopy with its low sensitivity has been used as a diagnostic technique in Ethiopia, searching alternative diagnostic methods which have better sensitivity should be a priority agenda. Objective . This study is aimed at evaluating the performance of diagnostic methods for Schistosoma mansoni in Amhara region. Methods . A cross-sectional study was conducted among 520 school children from October to December 2019 in Amhara region. The study participants were selected by a systematic random sampling technique. Stool samples were collected from each participant and processed via formol-ether concentration, Kato-Katz, and spontaneous tube sedimentation techniques. The data was entered into EpiData version 3.1, and analysis was done using SPSS version 20. The sensitivity, specificity, positive predictive value, and negative predictive value were calculated against the combined result as "Gold" standard. A kappa value was computed to measure the strength of agreement of the diagnostic methods. Results . The overall prevalence of Schistosoma mansoni was 20.2% using a combination of three methods. The prevalence of 8.3%, 12.9%, and16.3%, respectively, was recorded by using formol-ether concentration, Kato-Katz, and spontaneous tube sedimentation. The spontaneous tube sedimentation method (81.0%) had better sensitivity compared to Kato-Katz (63.8%) and formol-ether concentration (41.0%) methods in Schistosoma mansoni detection. Conclusion . The spontaneous tube sedimentation technique is more sensitive and has better detection rate to Schistosoma mansoni infection followed by the Kato-Katz technique. Therefore, updating the current diagnostic methods for Schistosoma mansoni could be a priority agenda to take action in schistosomiasis prevention and control.